Sistem Informasi Persediaan Barang Berbasis Web Pada Toko Berkah Bersama - Hardjono, Yusuf; Setianti, Novita (Teknikom: Teknologi Informasi, Ilmu Komputer dan Manajemen; Vol 10 No 1 (2025), 2025)
Problems with inventory are operational problems that are often faced by companies. If the amount of inventory is small and demand cannot be met, it can hamper the work process, as well as if the inventory is too large, this can result in losses to the company. Berkah Bersama  is a store that in managing inventory data still uses a manual system by being recorded in a ledger. In addition to taking a long time, there is no specific information that informs about the amount of stock, so that when the stock runs out, the shop owner must know when the transaction process occurs. The system that will be made is a web-based inventory information system using the PHP programming language which aims to facilitate the recording of incoming goods, the process of goods going out to making reports. The information system that will be developed will use the prototype method which consists of several steps, namely identify basic requirements, development initial prototype, user review and review and upgrade the prototype. This information system is online with the website address https://sabrinafashion.dorm18.site/.